Disappearing acts - McMillan, Terry (New York : Washington Square Press, 1989)
Franklin is a young black man, father of two, separated from his wife, who meets Zora, a struggling singer from Ohio. Neither is interested in commitment, but the chemistry is a powerful force.
Keywords: ROMANCE AND LOVE STORIES -- FICTION